La nature juridique du rescrit fiscal - Benmouhamed, SARA (Journal of Human Sciences, 2016)
The Finance law of 2012 introduced a new procedure that aims to guarantee legal security and stability through guarantees accorded to taxpayers in good faithand although the tax ruling is a concept that has been defined in réglementary texts, its application still raises some questions , including its legal status especially that  the answer to this question will permit us to better understand the regime which is applicable .